Intention to quit job among nurses working at a private tertiary care teaching hospital, Nepal - Prasad SharmaG, Ram; Rajbanshi, Laxmi; Prasad Singh, Jaya (Journal of Chitwan Medical College, 2024)
Background: Nurses’ turnover has disrupted the operational processes of health services, staffing arrangements, and hospital revenue. It is crucial for hospital managers to focus on nurses' attrition to understand the causes and consequences of their departure from the organization. This study explores perceptions of nurses leaving their current jobs Method: This cross-sectional study was conducted among nurses employed at Chitwan Medical College Teaching Hospital in Central Nepal. The study included all full-time nurses with at least one year of experience in the current organization, selected through consecutive sampling. Data were collected by using structured questionnaire for demographic details and nine other domains. Data were analysed using descriptive statistics. Result: Among 127 nurses surveyed, 73(57.5%) expressed an intention to quit their current job, higher among married nurses (62.9%), those without children (81.2%), critical care nurses (63.2%), and nurses with at least three years of experience (60.6%). Notably, the domains of schedule and working hours, manager, and work climate exhibited the highest intention to quit job with median percentages 66.7%, 65.7%, and 60% respectively. Conclusion: This study found that more than half (57.5%) of nurses had intention to leave their current jobs. The schedule and working hours, supervision, work climate was some of the intention to quit job, which highlights targeted strategies to address these issues to retain nurses.